(untitled) (Advances in Applied Mathematics and Mechanics, 2021)
The cold fluid flowing over two hot spheroids placed in a tandem arrangement was numerically studied via a GPU-based immersed boundary-lattice Boltzmann method (IB-LBM) model. The drag coefficient and average Nusselt number of both the two spheroids were obtained with the main influencing factors investigated. To validate the IB-LBM model, several numerical case studies containing one and two spheres were firstly conducted to reach the good agreement with the previously reported data. Then, a number of simulations were further carried out which were designed by changing the particle aspect ratio (1.0≤ Ar ≤4.0) and inter particle distance (1.5≤ l ≤7.0, where l = L/D, D stands for the volume-equivalent sphere diameter) as well as the Reynolds number (10 ≤ Re ≤200). Their influence on the momentum and heat transfer characteristics between the solid and fluid phases were fully discussed. Numerical results show that, for all the considered Reynolds numbers and aspect ratios, the individual and total drag coefficients and average Nusselt number increase with the inter particle distance. The inter particle distance has greater influence on the drag coefficient and average Nusselt number of the trailing particle than the leading one. The drag coefficient and average Nusselt number of the trailing particle are far less than the leading one under the same working conditions. The prediction correlations for the drag coefficient and average Nusselt number of both the two spheroids were established with low deviations. At last, the influence of the relative incidence angles between the two tandem spheroids on the momentum and heat transfer was studied. It is shown that the relative incidence angles play significant roles due to the change of the frontal area of the leading spheroid with these angles.